The facilitators' perspectives of delivering a 'Coping with Voices' group (Part 1). Issue 3 (3rd July 2022) - Kay, Gordon; Slattery, Maddy; Kendall, Elizabeth
ABSTRACT: Background: This multi-site study evaluated facilitator perspectives of a group-based program that brings together the common elements of cognitive behaviour therapy for psychosis (CBTp) with the knowledge and values of the peer led hearing voices networks (HVN). Twenty-two group facilitators were asked to complete a 58-item online survey which measured the usefulness, most important skills, benefits, acceptability and effectiveness of the Coping with Voices program. Methods: Aligning with a mixed-methods approach the survey consisted of open and closed-ended questions. The closed-ended questions were analysed using descriptive analysis and open-ended questions were analysed using thematic analysis. Results: The majority of facilitators reported the overall normalisation of voices and the use of a range of normalising strategies as the most useful aspects of the program. The most important skills used by facilitators were being understanding, non-judgemental and respectful and creating a safe space to discuss topics. The least important skills used by facilitators were using personal disclosure and motivational interviewing. Facilitators' comments illustrated a strong interest in using digital technologies in the preparation and delivery of the program. Discussion: This study contributes to a growing body of evidence that suggests hearing voices groups are beneficial, feasible and worthwhile.